PROPELLER SHAFT REDESIGN ON GRAN MAX 1.3 PICK UP VEHICLES - Army Ardiyanto; Kardiman -; Iman Dirja (Universitas Muhammadiyah Semarang, 2022)
The car component that will be discussed is a Propeller Shaft. The Propeller Shaft that will be discussed is the Propeller Shaft for the Daihatsu Gran Max 1.3 Pick Up. The task of this machine element 1 aims to determine safe and good axle planning. The material used to design the shaft is carbon steel for machine construction of cold finished steel rods for the shaft with the symbol S55C with a tensile strength of 66 kg/mm2. The results of the shaft planning calculations show that the design power is 51, 744 kW, the torsional moment is 8399,775 kg.mm, the allowable stress is 5.5 kg/mm2 . The shear stress that occurs is 0.22269201 kg/mm2 , from the calculation results it can be seen that the shear stress that occurs is smaller than the allowable stress, so it can be concluded that the planned shaft size is quite safe.